Persepsi Jemaat Korampotan Pondan Tentang Potensi Pendekatan Kelompok Sel dalam Mendorong Jemaat Beribadah - Sosinggih, Rosalina; Ruindungan, Leo Mardani; Parinsi, Niel; Bungalan, Jhon Efrendi (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
Worship is the central activity of the church, but many churches whose congregation members are less active in worship. Several studies have shown that the cell group approach can encourage church members to worship actively. The Banggai Protestant Independent Congregation (PJM-PB) of the Pondan Korampotan Congregation also faces the same problem, but until now, the cell group approach has not been used in ministry. This study examines the potency of the cell group approach in increasing the attendance of church members in worship at the Pondan Korampotan Congregation. The method used is qualitative, with interviews as a data collection technique. Data analysis uses reduction, display, and conclusion techniques. The number of informants involved was 13, including pastors, church boards and church members. The study results show that the cell group approach is very potential to be implemented in the Pondan Korampotan Congregation because all informants view this approach as essential and believe that if implemented in the congregation, it will encourage increased congregation member participation in worship. The reasons put forward to support this opinion include: 1) cell group makes it easier for God's servants in the congregation to reach all members, including members who are not active; 2) cell group provides space for all members to participate actively; 3) in the cell group, the relationship between members is intimate, mutually supportive, and sharing.